2021
DOI: 10.1111/nyas.14655
|View full text |Cite
|
Sign up to set email alerts
|

Sweetness is in the ear of the beholder: chord preference across United Kingdom and Pakistani listeners

Abstract: The majority of research in the field of music perception has been conducted with Western participants, and it has remained unclear which aspects of music perception are culture dependent, and which are universal. The current study compared how participants unfamiliar with Western music (people from the Khowar and Kalash tribes native to Northwest Pakistan with minimal exposure to Western music) perceive affect (positive versus negative) in musical chords compared with United Kingdom (UK) listeners, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 55 publications
(146 reference statements)
4
21
0
Order By: Relevance
“…An interesting case-in-point here is the history of the major third interval which is highly harmonic but became consonant only over time in Western music (see Hindemith, 1942;Tenney, 1988), familiarity (through frequency of occurrence) evidently driving its perceived consonance instead of an inherent acoustic 'harmonicity' effect. This latter observation is in line with cross-cultural research demonstrating a lack of preference for major chords (McDermott et al, 2016;Lahdelma et al, 2021) and major-key chord sequences (Athanasopoulos et al, 2021) in non-Western populations. As this recent cross-cultural research evidence suggests that harmonicity preferences may be restricted to the Western musical culture, it is possible that such preferences are learned both on an individual (Weiss et al, 2020) and on a cultural level (see through exposure.…”
Section: Is the Role Of 'Harmonicity' In Consonance Preferences Actually Familiarity With Tonality?supporting
confidence: 87%
See 3 more Smart Citations
“…An interesting case-in-point here is the history of the major third interval which is highly harmonic but became consonant only over time in Western music (see Hindemith, 1942;Tenney, 1988), familiarity (through frequency of occurrence) evidently driving its perceived consonance instead of an inherent acoustic 'harmonicity' effect. This latter observation is in line with cross-cultural research demonstrating a lack of preference for major chords (McDermott et al, 2016;Lahdelma et al, 2021) and major-key chord sequences (Athanasopoulos et al, 2021) in non-Western populations. As this recent cross-cultural research evidence suggests that harmonicity preferences may be restricted to the Western musical culture, it is possible that such preferences are learned both on an individual (Weiss et al, 2020) and on a cultural level (see through exposure.…”
Section: Is the Role Of 'Harmonicity' In Consonance Preferences Actually Familiarity With Tonality?supporting
confidence: 87%
“…Another recent cross-cultural research endeavor comparing the perception of chords across non-Western (two remote Northwest Pakistani tribes with limited exposure to Western music) and Western listeners echoes the findings of McDermott et al (2016). The Northwest Pakistani tribes did not indicate any preference for the consonant major triad but had a clear aversion to the highly dissonant chromatic cluster chord (Lahdelma et al, 2021).…”
Section: Harmonicity Reflects Acquired Aspects Of Consonance Preferencesmentioning
confidence: 88%
See 2 more Smart Citations
“…The cue-redundancy model was proposed based on the relationship between music and emotion in cross-cultural research (Balkwill and Thompson, 1999). Many cross-cultural studies have confirmed that participants were sensitive to the intended emotion aroused by unfamiliar music through attending to psychophysical cues (Argstatter, 2015;Cowen et al, 2020) such as tempo and rhythm (Balkwill et al, 2004;Fritz et al, 2009;Zacharopoulou and Kyriakidou, 2009;Laukka et al, 2013;Midya et al, 2019), complexity (Balkwill et al, 2004), harmonic dissonance (Athanasopoulos et al, 2021;Lahdelma et al, 2021), and tonality (Laukka et al, 2013;Egermann et al, 2015;Raman and Dowling, 2017;Midya et al, 2019). Timbre is one of the psychophysical cues that has a great impact on affect perception in crosscultural research, although not much research has been conducted on this.…”
Section: Introductionmentioning
confidence: 99%